2019
DOI: 10.1021/acs.jced.9b00245
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium of Systems Cyclohexene + Water + Cyclohexanone + N-Methyl-2-pyrrolidone (+Acetonitrile)

Abstract: The paper presents the results of the study of phase equilibrium in the system formed in the reaction of cyclohexene oxidation (cyclohexene + water + cyclohexanone + solvent). Pure N-methyl-2-pyrrolidone or binary mixture acetonitrile + Nmethyl-2-pyrrolidone was considered as a solvent. The method of studying was mathematical modeling on the base of the nonrandom two-liquid model. Thermodynamic-topological analysis was used to analyze the structure of the vapor−liquid equilibrium diagram. The mixture separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…This method is well-known and widely used to study the phase behavior of quaternary mixtures. 24 29 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This method is well-known and widely used to study the phase behavior of quaternary mixtures. 24 29 …”
Section: Resultsmentioning
confidence: 99%
“…The study of the VLE diagram was based on thermodynamic-topological analysis. This method is well-known and widely used to study the phase behavior of quaternary mixtures. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, based on the study of the physicochemical properties of a series of solvents, it was shown that 1-methylpyrrolidin-2one and N,N-dimethylacetamide are promising solvents. 6 When studying the reaction and separation constituents, the question of the quantitative composition of the mixture (the amount of reagent, solvent, water) is discussed. This question is of fundamental importance since the reaction mixture contains a catalytic system, which, after separation from the target product, must be returned to the stage of chemical transformation.…”
Section: Introductionmentioning
confidence: 99%